Insights into Charge Transfer at an Atomically Precise Nanocluster/Semiconductor Interface. Issue 20 (18th March 2020) - Wang, Yu; Liu, Xiao‐He; Wang, Qiankun; Quick, Martin; Kovalenko, Sergey A.; Chen, Qing‐Yun; Koch, Norbert; Pinna, Nicola
Abstract: The deposition of an atomically precise nanocluster, for example, Ag44 (SR)30, onto a large‐band‐gap semiconductor such as TiO2 allows a clear interface to be obtained to study charge transfer at the interface. Changing the light source from visible light to simulated sunlight led to a three orders of magnitude enhancement in the photocatalytic H2 generation, with the H2 production rate reaching 7.4 mmol h −1  gcatalyst −1 . This is five times higher than that of TiO2 modified with Ag nanoparticles and even comparable to that of TiO2 modified with Pt nanoparticles under similar conditions. Energy band alignment and transient absorption spectroscopy reveal that the role of the metal clusters is different from that of both organometallic complexes and plasmonic nanoparticles: A type II heterojunction charge‐transfer route is achieved under UV/Vis irradiation, with the cluster serving as a small‐band‐gap semiconductor. This results in the clusters acting as co‐catalysts rather than merely photosensitizers. Abstract : Multitasking : Metal nanoclusters are not merely photosensitizers, they can also act as co‐catalysts under appropriate conditions. Deposition of the atomically precise nanocluster Ag44 (thiolate)30 onto a large‐band‐gap semiconductor such as TiO2 led to a type II heterojunction charge‐transfer route being achieved on irradiation with UV/Vis light, with the cluster serving as a small‐band‐gap semiconductor, rather than merely a photosensitizer.